Analisis Struktur Ruang Tari Puan Huma - Harina, Dera (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Puan Huma Dance is a dance art that expresses the important role of women in farming activities, especially in the process of planting rice in rice fields. This research aims to analyze the spatial structure in the Puan Huma Dance based on the spatial concept of dance introduced by Y. Sumandiyo Hadi, which includes positive-negative space, level, direction, floor pattern and dimensions. This analysis uses a case study method, which allows in-depth research on the spatial elements in this dance. The research results show that the movements in the Puan Huma Dance are not only an aesthetic element, but also an effective medium in expressing cultural values and depicting the lives of dedicated farming women. The use of positive and negative space, as well as varying levels in movement, creates a deep and interesting visual dynamic. Additionally, the direction of movement and floor patterns convey a strong narrative about women’s experiences in agriculture. The conclusion of this research emphasizes the important role of women in farming and efforts to preserve culture through the art of dance. By understanding more deeply the movements and meaning of the Puan Huma Dance, it is hoped that society can appreciate the contribution of women in agriculture and community life as a whole. It is also hoped that this research can contribute to the development of creative dance that still maintains local cultural roots.